Polymer-Based Functional Materials Loaded with Metal-Based Nanoparticles as Potential Scaffolds for the Management of Infected Wounds - Xhamla Nqoro; Raymond Taziwa (MDPI AG, 2024)
Wound infection due to bacterial invasion at the wound site is one of the primary challenges associated with delayed wound healing. Microorganisms tend to form biofilms that protect them from harm, leading to their multidrug resistance. The alarming increase in antibiotic resistance poses a threat to wound healing. Hence, the urgent need for novel wound dressing materials capable of managing bacterial infection is crucial for expediting wound recovery. There is considerable interest in polymeric wound dressings embedded with bioactive substances, such as metal-based nanoparticles, as potential solutions for treating microbially infected wounds. Metal-based nanoparticles have been widely used for the management of infected wounds due to their broad antimicrobial efficacy. This review focuses on polymer-based and bioactive wound dressings loaded with metal-based nanoparticles like silver, gold, magnesium oxide, or zinc oxide. When compared, zinc oxide-loaded dressings exhibited higher antibacterial activity against Gram-positive strains and silver nanoparticle-loaded dressings against gram-negative strains. However, wound dressings infused with both nanoparticles displayed a synergistic effect against both strains of bacteria. Furthermore, these dressings displayed antibiofilm activity and the generation of reactive oxygen species while accelerating wound closure both in vitro and in vivo.